Luhmann's theory of education - Kolenc, Janez (Šolsko polje, 2012)
When we speak of education, we usually think about international activities, which try to develop the abilities (competences) of an individual, which then lead to the some kind of social action. This starting point has the foundation in the following results of researching the problem of education. The notion of education as a social activity is founded on the premises, which have come about from the social-historical circumstances and from the theoretical reflection about the human being as a social entity as well as from the theory of social change. The need to clarify the notion of education and what could be expected from education comes from taking a second look at how the relationship between human beings and society can be conceptualised.
Keywords: Luhmannn's theory of education; vzgoja in izobraževanje; education; pedagoške teorije